Alternatif Pengelolaan Bantuan Operasional Kesehatan untuk Peningkatan Kesehatan Ibu dan Anak Cakupan K1-K4 - Yolandia, Rita Ayu; Hardiana, Hedy (Jurnal Ilmiah Kebidanan Indonesia, 2019)
Health Operations Assistance fund management for improving maternal and child health in particular in K1 – K4 is not optimal, Because most of the management of BOK funds are used for supporting activities and public health efforts, in this case the central government assistance to local governments to support the operation of Puskesmas in the framework of the achievement of health programs National priorities, in particular preventive promotive activities as part of public health efforts. This research is a qualitative study with a case study approach. The informant in this research includes the head of Public health service, head of Puskesmas and midwife of Kordinator as key informant. Data collection is done by the method of interview indepth. The findings in this study are the 4 main problems of human resources limitation, especially in the management of health operations assistance and increase the coverage/activities of maternal and child health in each area of Puskesmas, Workload of human Resources health care which is not comparable to the number of resources, is limited to the health operational assistance for the financing of activities and the delay of health operations assistance for liquids. This is due to reports of late health clinics. Based on the results of the analysis of Urgency, Serious and Growth (USG), and Strategies Planning Matrix (QSPM) obtained the priority of alternative proposed operational policy recommendations to increase the scope of K1-K4 on maternal and child health program: proposed Alternative recommendation is selected BOK's fund allocation policy in particular for KIA, the proposal for routine activities of GEMPOR S2 policy (completion of the report 1 Hour 1 day).